Studi Sebaran Kawasan Resapan (Permeable Area) Pada Berbagai Tipe Penggunaan Lahan - Harisuseno, Donny; Rispiningtati, Rispiningtati; Andawayanti, Ussy; Suhartanto, Ery; WWS, Anggara; Hari Oktavianto, Sapto Dwi (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2013)
Development in an urban area as an impact of high density population is always in line with landuse change. Alteration of landuse from permeable area into impermeable area give an impact on reducing amount of rainfall which infiltrate into soil. This situation directy will cause an inundation problem in an urban area.The research was located in Brantas Sub Watershed which was administered include in the Klojen District, Malang. The study was focussed on estimate spatially an infiltration area map by considering various of landuse type. Analyses of infiltration area spatially was performed by applying hydrological model which integrated with Geographical Information System.The result showed that there was difference response on each landuse type in term of infiltration rate which occurred. Direct field measurement was conducted on each landuse type and exhibited level of infiltration rate from least one to biggest one, namelygreen open area (0,172 mm/min), shrub (0,068 mm/min), commercial area (0,043 mm/min), social and public facility area (0,032 mm/min) and residential area (0,031 mm/ min), respectively. Spatial analyses of infiltration areausing hydrological model KINEROS by considering 5 year design rainfall showed percentage of infiltration area 8,15% (for landuse year 2000), 7,82% (for landuse year 2005), and 6,6% (for landuse year 2010(, respectively.It can be known that the percentage of infiltration area was decrease from year 2000 to 2010. These results were hoped to be an important information for city planning especially in term of land and water conservation in urban area.Keywords: KINEROS model, Infiltration, Infiltration Area